What Not to Do for Bed Bugs/Que No Hacer contra las Chinches - Faith M. Oi; Jennifer Gillett-Kaufman; Eddie Connor; Marty Overline; Brian Taggart; Louis Witherington (EDIS)
In desperate attempts to eliminate bed bugs, people often turn to home remedies that can be fatal. Here is a list of what not to do for bed bug control.